Pengaruh Team Work dan Disiplin Kerja Terhadap Produktivitas Kerja Pegawai pada Bank NTB Syariah Bima - Aulia Rizqi Maretania; Firmansyah Kusumayadi; Kartin Aprianti (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study examines the influence of teamwork and work discipline on employee work productivity at Bank NTB Syariah, Bima Branch. A Likert scale was employed to measure respondents' attitudes, perceptions, and opinions regarding statements related to teamwork, work discipline, and work productivity. The study involved a sample of 30 respondents. The findings lead to the conclusion that teamwork has a significant influence on employee work productivity at Bank NTB Syariah, Bima Branch; work discipline has a significant influence on employee work productivity at Bank NTB Syariah, Bima Branch; and both teamwork and work discipline significantly influence employee work productivity at Bank NTB Syariah, Bima Branch.